Leadership training as an alternative to neoliberalism: A model for community development. Issue 4 (8th August 2021) - García, Ivis
ABSTRACT: In recent decades, cities have experienced dwindling state resources and growing socioeconomic inequalities—many scholars have identified this change as neoliberalism. Although these changes have generated much debate, not a lot of scholarship has tried to present alternatives. This article uses the Westside Leadership Institute (WLI) in Salt Lake City, Utah, as a case study to understand what can be done at low cost to address historically disadvantaged communities and improve their conditions. Through leadership development, participants develop cognitive, interpersonal, and strategic skills. They also form a symbiotic relationship with anchor institutions, a Community Development Corporation and the University of Utah. Using data from interviews, focus groups, and surveys, this article examines how residents have applied what they learned in the WLI to create social change at the local level. Although small-scale community development, the WLI has proven to be effective at building and sustaining indigenous leaders, who in turn push a progressive agenda forward.